2020
DOI: 10.14710/jitaa.45.4.253-260
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNP T125A on KiSS1 gene with reproduction hormone levels in Kaligesing goat

Abstract: The objective of this study was to assess the association of KiSS1 gene polymorphism with reproductive traits in Kaligesing goat. Genotypes of 48 ewes aged three years old were determined using PCR-RFLP and DNA sequencing. Sixteen out of 48 samples were monitored for the estrus cycle and determined their 17β-estradiol and progesterone levels using ELISA method. The results showed that KISS1 gene in the studied population was polymorphic with one single nucleotide polymorphism (SNP T125A). Then SNP was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…The hormone estrogen increases with follicle growth, as it is produced by granulosa cells that form the follicle wall (Ramli et al, 2016;Astuti et al, 2020). The results of this study are similar to research on the Kiss1 gene locus by Hardyta et al (2020) in kaligesing goats, which found no association between estradiol levels and the Kiss1 gene. Henceforth, studying the association of hormone concentrations in larger samples and at other SNP loci of the FSHR and PRL genes is necessary.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The hormone estrogen increases with follicle growth, as it is produced by granulosa cells that form the follicle wall (Ramli et al, 2016;Astuti et al, 2020). The results of this study are similar to research on the Kiss1 gene locus by Hardyta et al (2020) in kaligesing goats, which found no association between estradiol levels and the Kiss1 gene. Henceforth, studying the association of hormone concentrations in larger samples and at other SNP loci of the FSHR and PRL genes is necessary.…”
Section: Resultssupporting
confidence: 84%
“…Estradiol concentrations measured from 15 dairy cows during estrous obtained an average of 60.06±33.25 pg/ml. This result is almost the same as the estradiol concentrations during estrous reported in Bali cattle 55.00 ± 4.33 pg/ml (Suartini et al, 2013); 63.16 pg/ml (Laksmi and Trilaksana, 2020); in beef cattle 40.06 -67.80 pg/ml (Astuti et al, 2020); in SimPO cattle 69.30±27.20 pg/ml; dairy cattle 61.00 ±19 pg/ml (Firdausyia, 2018); and in kaligesing goats 50.12±61.26 pg/ml (Hardyta et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of this, these SNPs have the potential to serve as novel molecular markers for determining the litter size of goat (Table 1). [12][13][14][15][16][17][18][19][20][21][22] Polymorphisms and frequency distributions of GDF9 gene The SNPs of GDF9 genes were identified, and litter size traits were analyzed in four Indonesian goats (Saanen, Bligon Kacang and Kejebong). The results of the PCR restriction fragment length polymorphism (RFLP) analysis revealed four new polymorphisms in all three GDF9 genes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research in Indonesia characterized the polymorphisms of KISS1 gene intron 1 and exon 1 of Ettawa Grade (EG), although the researchers could not find the association with LS and other reproductive traits (Mulyono et al, 2019;Hardyta et al, 2020). However, to make the best use of limited selection funds, specific indigenous breeds must be prioritized for selection.…”
Section: Introductionmentioning
confidence: 99%